Digital PCR characterizes epithelial cell populations in murine duodenal organoids - Karla Acosta-Virgen; Hugo David González-Conchillos; Gabriela Vallejo-Flores; Lizbeth Iliana Salazar-Villatoro; Ernesto Guerrero-Sánchez; Adolfo Martínez-Palomo; Martha Espinosa-Cantellano (PLoS ONE, 2025)
Three-dimensional cultures are powerful tools to recapitulate animal and human tissues. Under the influence of specific growth factors, adult stem cells differentiate and organize into 3D cultures named organoids. The molecular phenotyping of these structures is an essential step for validating an organoid model. However, the limited number of organoids generated in culture yields very low amounts of genetic material, making phenotyping difficult. Recently, digital PCR (dPCR) techniques have become available for the highly sensitive detection of genetic material at low concentrations. The aim of this work was to apply dPCR to the identification of the various cell populations expected to be present in murine duodenal organoids. Results show the potential use of dPCR as a genetic characterization tool for organoids.